Knowledge, understanding and consumer practices of UP students related to nutrition labels - Zerrudo, Adeline Rose A.
4aThe market is filled with various options for food products with different claims and features, thus nutrition in information is increasingly becoming a potent force in empowering consumers in making that right choice in food. Nutrition is salient in determining the well-being of an individual, thus nutrition labels should be utilized regularly to address a number of health concerns. This research is a descriptive study of a relationship nutrition knowledge, understanding of nutrition labels and consumer practices. The respondents include 73 randomly selected residents of Kalayaan and Yakal dormitories of the University of the Philippines, Diliman. A Nutrition Information Test survey questionnaire determined participants' knowledge on nutrition, understanding of nutrition labels, and the regularity of their practices in using these labels. Results showed satisfactory nutrition information of the participants. On the other hand, majority do not have desirable practices with the use of nutrition information. Using Pearson's correlation, nutrition knowledge does not correlate with understanding of nutrition information. Understanding these labels does not require extensive knowledge of nutrition. Meanwhile, nutrition knowledge has a weak relationship with desirable practices in nutrition information, indicating that knowledge, at some point, translates to practice. In contrast, understanding of labels does not have a correlation with the practice of using these nutrition labels. Finally, all practices have a weak to strong correlation among each other, suggesting that one practice may pave the way for other practices. This study recommends an intensive campaign to improve food habits of consumers by ensuring presence of nutrition labels on food products, as well as developing courses that will enhance the consumers' knowledge in nutrition. Possible studies may include an analysis of nutrition knowledge and consumer practice vis-a-vis the health status and physical make-up of obese or undernourished children and even the elderly.